QUANTITATIVE ASPECTS OF METAZOAN PARASITES OF MOLE CRAB EMERITA ANALOGA (STIMPSON) (DECAPODA, HIPPIDAE) FROM CHORRILLOS, LIMA, PERU - Iannacone, Jose (2007)
Some components of 860 specimens from Emerita analoga acquired in the Chorrillos Fismarket (Lima,Peru) were investigated between October 1996 and September 2007. From the crabs collected, 317 weremales and 543 were females. Mole crabs showed a cephalothorax length mean 2.77 ± 0.84. Metazoanparasites were collected and counted employing conventional techniques, including outer body surface,hemocoel, gut and hepatopancreas. One thousand two hundred sixty-seven specimens were collected during all the survey, with a mean abundance of 1.47 (1-22). The mean parasite species was 1.14 (1-3). Three hundred fifty-one hosts were not parasited. Four hundred thirty-two hosts (50.2 %) showed infection with one parasite species, and seventy-six (8.8 %) and one (0.1 %) had multiple infection, 2 and 3 parasite species, respectively. Three parasites: Profilicollis altmani (Perry, 1942) Van Cleave, 1947 (Acantocephala) (prevalence = 55.3 %; mean intensity = 2.21), Proleptus sp .(Nematoda) (prevalence = 12.1 %; mean intensity = 2.01) and an unidentified trypanorhynch tapeworm (Cestoda) (prevalence = 0.69 %; mean intensity = 1) were found. Effect of the sex and cephalothorax length of E. analoga on mean intensity, abundance of Infection and prevalence of P. altmani and Proleptus sp. were not observed. Only a relation of sex with mean intensity of infection with Proleptus sp. was found.